Legal Consequences of Abuse of Circumstances in Sale and Purchase Binding Agreement on Land and Building - Susilowardani, Susilowardani (Universitas Kuningan, 2024)
This study aims at understanding the legal consequences of abuse of circumstances (misbruik van omstandigheden) in sale and purchase binding agreements on land and buildings. This study used a descriptive-analytical method, including the description, explanation, and analysis of the issues that occurred, followed by drawing conclusions to find the correct answers as solutions to the problems being analyzed. The results showed that, in practice, incidents indicating a defect of will, such as fraud and duress, are often encountered. This can be referred to as abuse of circumstances or misbruik van omstandigheden, leading to the issue of the legal consequences of abuse of circumstances in sale and purchase binding agreements on land and buildings. Yet, regulation on misbruik van omstandigheden (abuse of circumstances) has not been established in law. The legal consequence of the transfer of land rights carried out based on abuse of circumstances is a violation of the subjective condition of the agreement, namely the agreement of the parties, so the agreement can be annulled. Considering the numerous cases of abuse of circumstances, the authorities are required to consider and formulate applicable law to further strengthen the doctrine of abuse of circumstances used by judges.